Discovering the lived experiences of graduate students in the virtual space: Reflections and lessons from a phenomenological inquiry - Ernesto Cordero Collo, Jr. (Informasi, 2021)
The COVID-19 pandemic has radically reshaped the academic life of graduate students and revealed the inequities in the traditional education system in the Philippines. This study is a qualitative navigation of the lived accounts of development communication (devcom) graduate students at the University of the Philippines Los Baños. It foregrounds devcom as a field of theory and practice in honor of its pioneer Professor Emeritus Nora C. Quebral and her contribution to the ferment of the field. The credence of phenomenology informed the direction of this research in addressing a paucity of literature that examines the experiences of graduate students on remote learning within the current milieu. The transition of academia into a new phase of development surfaced stories of personal and academic struggles. As social beings, they engage virtual and real spaces in coping that redirect them to a sense of purpose and semblance of normalcy at a time of uncertainties. To address their recurring and emerging conditions is the cultivation of institutional support and online forms of communication support as two pivotal forms of their reflective recommendations. Drawing from the participants’ reflections, I developed a schema that investigates the intersectionality of their struggles, coping, and recommendations towards a conducive remote learning milieu.